2010
DOI: 10.1111/j.1439-0426.2010.01502.x
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of introducing the invasive amphipod Gmelinoides fasciatus into large shallow Lake Peipsi: present distribution and possible effects on fish food

Abstract: The objective of the study was to assess the effect of the Baikalian amphipod Gmelinoides fasciatus, a successful invader into Europe, as a fish food source in Lake Peipsi to where it was introduced in the 1970s. In 2002-2006, the littoral macrozoobenthos was studied along 17 transects (0.1-4 m depth, 384 quantitative samples) to determine the recent distribution of G. fasciatus and its share in the benthic community. Earlier records on the littoral macrozoobenthos from the years 1970, 1980, 1990 and 2000 wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 32 publications
0
5
0
1
Order By: Relevance
“…In Lake Peipsi, G. fasciatus was most abundant on coarse particle substrates, most notably gravel and sand, while their abundance on silt was minimal (Kangur et al 2010). This result suggested that coarser substrates provided the best refuge from predators.…”
Section: )mentioning
confidence: 94%
See 2 more Smart Citations
“…In Lake Peipsi, G. fasciatus was most abundant on coarse particle substrates, most notably gravel and sand, while their abundance on silt was minimal (Kangur et al 2010). This result suggested that coarser substrates provided the best refuge from predators.…”
Section: )mentioning
confidence: 94%
“…In addition to outcompeting native amphipods, other important shifts in native communities have been recorded. The littoral area (< 4 m depth) of Lake Peipsi accounts for approximately 5% of the lake bottom, whereas G. fasciatus represents approximately 43% of total macrozoobenthos abundance (Kangur et al 2010). Furthermore, at a suitable depth (< 0.2 m) and substrate (gravel and sand), G. fasciatus comprises up to 97% of total macrozoobenthos abundance, excluding other macroinvertebrates and effectively forming a zoobenthos "monoculture" (Kangur et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…В последние десятилетия активно расселяется по всей Евразии, имеются многочисленные сведения о нахождении его в озерах (Ладожское, Псковско-Чудское), волжских водохранилищах, водохранилищах Ангарского каскада, в водоемах бассейна оз. Байкал (Panov, 1996;Basova, 2002;Berezina, Strelnikova, 2010;Kangur et al, 2010;Kurashov et al, 2012). Всеядность G. fasciatus, высокая подвижность рачков и способность к горизонтальным ациклическим миграциям повышают возможность сохранения популяций при воздействии неблагоприятных факторов и способствуют быстрому и успешному освоению разнотипных водоемов (Biological invasions …, 2004).…”
unclassified
“…Although many non‐native species are beneficial to humans (e.g. Gozlan, 2008; Arbačiauskas et al., 2010, this issue), a relatively small, but significant, proportion of them becomes invasive (Wolter and Röhr, 2010, this issue) and produces far‐reaching adverse impacts on native species and ecosystems (Britayev et al., 2010, this issue; La Porta et al., 2010, this issue; Kangur et al., 2010a, this issue; Kangur et al., 2010b, this issue). This can lead to significant economic losses and even pose risks to human health (Pimentel, 2000).…”
mentioning
confidence: 99%